KETERAMPILAN BERBAHASA MELALUI PENDEKATAN ACTIVE LEARNING ANAK TK BINA KALAM KECAMATAN PAKONG KABUPATEN MALANG - Anggraeni, Felia Putri; Gupita, Norma (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
Early childhood education (PAUD) is a level of education prior to basic education which is a coaching effort aimed at children from birth to the age of 6 years. This study aims to describe the process of implementing learning, the impact of development, supporting factors and inhibiting factors in the development of language skills through an Active Learning approach to children at Kindergarten Bina Kalam Pakong-Malang. The research method uses qualitative methods with descriptive research types. Sources of data obtained by means of the method of observation (observation), interviews and documentation. The results of the study show that the development of language skills includes listening, reading, speaking and writing. The method selection technique will have an impact on the ability to have self-confidence when talking actively to people around you. The supporting factors are related to the fulfillment and selection of appropriate learning media. Meanwhile, the inhibiting factors regarding the need for study time in children. Suggestions for research on academic needs related to language skills in children. It will be more supportive if it is harmonized if the application is supported by learning when it is done at home, such as building communication with parents and children.